Welcome to Scribd, the world's digital library. Read, publish, and share books and documents. See more
Download
Standard view
Full view
of .
Save to My Library
Look up keyword
Like this
158Activity
0 of .
Results for:
No results containing your search query
P. 1
solution manuals introduction to real analysis( Bartle and Sherbert)

solution manuals introduction to real analysis( Bartle and Sherbert)

Ratings:

2.5

(2)
|Views: 20,094 |Likes:
Published by Sanjeev Shukla
These notes cantain only few solved question of bartle and sherbert book i'll upload all solutions very soon.....
These notes cantain only few solved question of bartle and sherbert book i'll upload all solutions very soon.....

More info:

Published by: Sanjeev Shukla on Aug 23, 2010
Copyright:Attribution Non-commercial

Availability:

Read on Scribd mobile: iPhone, iPad and Android.
download as DOC, PDF, TXT or read online from Scribd
See more
See less

02/13/2014

pdf

text

original

 
SOLUTION CHAPTER 2.2INTRODUCTION TO REAL ANALYSISBARTLE AND SHERBERT
Definition-: (Absolute value )Absolute value of a real number ‘a’ is denoted by │a│ and isdefined as-a if a≤ 0│a│=a if a 0there are few properties of absolute value which can be provedvery easily here I’ll just write them I won’t prove them you can askme if you are not able to prove them you can mail messsshukla112@gmail.comProperty 1 Property 3│a│= max{ a, -a} sqr(│a│) = sqr(a)=sqr(-a) Property 2 Property 4│a+ b│ │a│ + │b│ │a│ = │-a│Now we have some basic idea about absolute value, we can nowsolve the questions….
Geometrical meaning of│a│-:
│a│ is distance of real number ‘a’ from 0.And │a- b│ is distance between ‘a’ and ‘b’Q1(a)-: To show that │a│ =√ sqr(a)Proof-:Case 1 when a 0 we have on the L H S │a│= a
sqr( │a│) = sqr(a) 
│a│ = sqr(a) (taking square root)
 
Case 2 a≤ 0 in that case we have │a│= -a
sqr( │a│) = sqr(-a) = sqr(a)
│a│ = sqr(a) (taking square root)Q1(b)-:│a/b│=│a│
/
│b│Sqr (│a/b│) = sqr(a/b) = sqr(a)/sqr(b) = sqr( │a│)/ sqr( │b│)= sqr(│a│
/
│b│)=> │a/b│ = │a│
/
│b│ (taking +ve square root)Q2 -:│a+ b│ = │a│ + │b│ Iff ab ≥ 0Proof-:First let us assume that │a+ b│ = │a│ + │b│To show that-: ab ≥ 0As │a+ b│ = │a│ + │b│
sqr(│a+ b│) = sqr(│a│ + │b│)
sqr(a+b) = sqr(│a│) + sqr(│b│) +2│a││b│
sqr(a)+sqr(b)+2ab= sqr(a)+sqr(b)+2│ab│using facts that │a││b│=│ab│and sqr(│a│) = sqr(a)now using cancelation laws we have that
 
2ab=2│ab│
ab=│ab│
ab ≥ 0conversely assume that ab ≥ 0to show that -: │a+ b│ = │a│ + │b│consider L H SWe have sqr(│a+ b│)=sqr(a+b)=sqr(a)+sqr(b)+2ab( as sqr(│a│) = sqr(a) ) => sqr(│a+ b│)=sqr(│a│)+sqr(│b│)+2│ab│( as ab ≥ 0 therefore ab=│ab│)=> sqr((│a+ b│)= sqr(│a│)+sqr(│b│)+2│a││b│
sqr(│a+ b│)= sqr(│a│ + │b│)
│a+ b│ = │a│ + │b│(Taking +ve square root)Q3 Given x,y,z in R with x≤ z, show that │x-y│+│y-z│=│x-z│iff x≤ y≤ zproof-:firstly assume that x≤ y≤ zto show that -: │x-y│+│y-z│=│x-z│consider L H SWe have │x-y│= -x+y ( becoz x≤ y => │x-y│= -( x-y) )Also │y-z│= -y+z ( becoz y≤ z =>│y-z│= -(y-z))Therefore │x-y│+│y-z│= -x+y -y+z = z- x = │z-x│ (“ ,“ x≤ z)=> │x-y│+│y-z│=│x-z│ (“ ,“ │a│ = │-a│)

Activity (158)

You've already reviewed this. Edit your review.
Maram Salahat added this note
How I can Download this >>> :(
Maram Salahat liked this
1 thousand reads
1 hundred reads
Aryan Patel liked this
Alexander Lopez liked this
MCSlocoloco liked this
Leandro Ribeiro liked this

You're Reading a Free Preview

Download
/*********** DO NOT ALTER ANYTHING BELOW THIS LINE ! ************/ var s_code=s.t();if(s_code)document.write(s_code)//-->